PENGARUH KUALITAS PELAYANAN DAN EFEKTIVITAS PELAYANAN DARI MESIN CUSTOMER SERVICE DIGITAL BCA TERHADAP KEPUASAN PELANGGAN: Studi Pada Nasabah Bank BCA di DKI Jakarta - Alfie Tandiana Halim (2022)
This study uses quantitative methods to prove the influence of service quality and service effectiveness either partially or simultaneously on customer satisfaction. This study uses 100 respondents from customers who use the BCA DKI Jakarta Digital Customer Service Machine as primary data, and secondary data obtained by researchers through various references related to this research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that the results are (1) service quality has a positive and significant effect on customer satisfaction, (2) service effectiveness has a positive and significant effect on customer satisfaction, and (3) service quality and service effectiveness simultaneously affect customer satisfaction.